Jesus : A Very Short Introduction - Bauckham, Richard (Oxford, New York Oxford University Press, 2011)
Two billion people today identify as Christians, with the implication that Jesus is the focus of their relationship with God, and their way of living in the world. Such followers of Jesus are now more numerous and make up a greater proportion of the world's population than ever before. Despite its decline in the West, Christianity is rapidly increasing in areas such as Africa and China. Richard Bauckham explores the historical figure of Jesus, evaluating the sources and concluding that they provide us with good historical evidence for his life and teaching. In order to place Jesus in his prope.
Include Index and Illustration
Keywords: Christology -- Jesus Christ